F17 The use of an accelerometer to evaluate the performance of timed up and go test in pre-symptomatic and symptomatic huntington's disease. (16th November 2010) - Khalil, H; Dalton, A; van Deursen, R; Rosser, A; Laighin, G Ó; Busse, M
Abstract : Background: The timed Up and Go (TUG) test is a widely used measure of mobility and risk of falls in older adults and in Huntington's disease (HD).1 The single outcome of the test is its duration. Therefore, the test does not capture subtle differences in the test performance and seems not to be sensitive in detecting deficits at early stage HD.2 Aim: This study aimed to quantify measures of the TUG performance in symptomatic and pre-symptomatic HD using an accelerometer and examine the responsiveness of these measures. Methods: 5 pre-symptomatic (PHD), 10 symptomatic (SHD), and 6 healthy controls (HC) (age (mean±SD) 41±10; 57±10; 48±17 years respectively) participated in the study. Participants wore an accelerometer attached to the sternum whilst performing the TUG. Total TUG duration and Sit to stand and Stand to sit durations were extracted from the sensor. Measures of range and slope for sit to stand and stand to sit were also calculated3 . Differences between groups were examined using One way ANOVA. When significant differences were identified post-hoc analyses were conducted using Tukeys test. Results: TUG duration showed no significant differences between the groups (P=0.1). However, all other measures were significantly (P<0.01) worse in SHD when compared with PHD and HC. Additionally, sit to stand and stand to sit slopes were significantly worse in PHD when compared with HC (P<0.05). Conclusion: In contrast with the TUG duration, the accelerometer derived measures of Sit to stand transitions in the TUG test were responsive to group differences in HD. The accelerometer therefore, can be used to produce objective measures of disease specific features that could not be quantified using simple visual analysis. The slope measures were able to detect changes in PHD and therefore have potential for use in monitoring the disease progression and response in therapeutic trials.